Expression of the p53 inhibitors MDM2 and MDM4 as outcome predictor in muscle-invasive bladder cancer - Kriegmair, Maximilian; Steidler, Annette; Weis, Cleo-Aron Thias; Erben, Philipp (Anticancer research, 2016)
Aim: To evaluate the prognostic role of the p53-upstream inhibitors MDM2, MDM4 and its splice variant MDM4-S in patients undergoing radical cystectomy (RC) for muscle-invasive bladder cancer (MIBC). Materials and Methods: mRNA Expression levels of MDM2, MDM4 and MDM4-S were assessed by quantitative real-time polymerase chain reaction (qRT-PCR) in 75 RC samples. Logistic regression analyses identified predictors of recurrence-free (RFS) and cancer-specific survival (CSS). Results: High expression was found in 42% (MDM2), 27% (MDMD4) and 91% (MDM4-S) of tumor specimens. Increased MDM2 expression was significantly associated with higher tumor stage (p=0.05) and lymphovascular invasion (LVI) (p=0.041). In the univariate analysis, low MDM4 expression (hazard ratio (HR)=5.93; p=0.002; HR=3.00; p=0.047), but not MDM2 (HR=1.63; p=0.222; HR=1.59; p=0.27), were associated with RFS and CSS. In the multivariate analysis, the combination of low MDM4 and high MDM2 was significant for RFS and CSS (HR=14.9; p=0.001; HR=5.63; p=0.019). Conclusion: The combination of MDM2 and MDM4 expression is an independent predictor in patients undergoing RC for MIBC.
Gesehen am 10.07.2019